2007
DOI: 10.1002/arch.20167
|View full text |Cite
|
Sign up to set email alerts
|

Female sex pheromone suppression and the fate of sex‐peptide‐like peptides in mated moths of Helicoverpa armigera

Abstract: Insect males produce accessory gland (MAG) factors that are transferred in the seminal fluid to females during copulation, and elicit changes in the mated female's behavior and physiology. Our previous studies showed that the injection of synthetic Drosophila melanogaster sex-peptide (DrmSP) into virgin females of the moth Helicoverpa armigera causes a significant inhibition of pheromone production. In this and other moth species, pheromone production, correlated with female receptivity, is under neuroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Genetic manipulation of SP-related genes has shown that SP causes some changes in the feeding behavior of adult female D. melanogaster immediately after mating (Kubli and Bopp, 2012). In addition, SP-like peptides have also been found in some insect species such as Helicoverpa armigera (Nagalakshmi et al, 2007). In H. armigera an SP-like peptide and its receptor mediate pheromone biosynthesis and re-mating rejection behavior against courting males (Nagalakshmi et al, 2007; Hanin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic manipulation of SP-related genes has shown that SP causes some changes in the feeding behavior of adult female D. melanogaster immediately after mating (Kubli and Bopp, 2012). In addition, SP-like peptides have also been found in some insect species such as Helicoverpa armigera (Nagalakshmi et al, 2007). In H. armigera an SP-like peptide and its receptor mediate pheromone biosynthesis and re-mating rejection behavior against courting males (Nagalakshmi et al, 2007; Hanin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SP-like peptides have also been found in some insect species such as Helicoverpa armigera (Nagalakshmi et al, 2007). In H. armigera an SP-like peptide and its receptor mediate pheromone biosynthesis and re-mating rejection behavior against courting males (Nagalakshmi et al, 2007; Hanin et al, 2011). SP and SP-like peptides are not conserved across insect species.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of pheromones in all the cases studied so far depends on neural mechanisms. In invertebrates, e.g., secretion of pheromones is neurohumorally regulated by neuropeptides such as PBAN (Christensen et al, 1991;Abernathy et al, 1996;Teal et al, 1999;Groot et al, 2005;Nagalakshmi et al, 2007), whose pheromonotropic effect is mediated by a receptor that is produced in the form of three subtypes by alternative splicing (Kim et al, 2008).…”
Section: Recruitment Of Sex Pheromones In Salamandersmentioning
confidence: 99%
“…This is unexpected, since SP itself is not well conserved. Apart from a few Drosophila species, SP-like peptides have only been identified in the moth Helicoverpa armigera [20][21][22].…”
Section: Introductionmentioning
confidence: 99%